Privacy in the Converged Communications Platform - Gita, Radhakrishna (2008)
People care about their personal privacy and have a right to expect that their personal details remain confidential. Yet almost every organization we deal with in our daily lives holds some personal information about us. The convergence of telecommunications, broadcasting, data communication, multimedia and other related technologies and services has increased the ease with which personal data can be gathered, exchanged and transmitted to various buyers of information. These capabilities raise a number of legal issues relating to the regulation of personal privacy and data protection. This paper looks at privacy issues in relation to the fast developing convergence technology in the telecommunication industry. It examines the sources of threats to privacy, the existing regulatory and legal regime in Malaysia and recommends possible strategies to avoid privacy risks.